Supporting all learners through high quality early childhood curricula: STREAMin3 implementation across Virginia - Clayback, Kelsey Ann; Williford, Amanda; Vitiello, Virginia; Matthew, Kate Lynn (Frontiers in Education, 2024)
IntroductionCurricula are an essential component of high-quality early learning experiences. Unfortunately, many early childhood educators face challenges in accessing evidence-based curricula, and implementation fidelity to curriculum is often poor without aligned support, including professional development for educators. This is especially true for educators within family day homes and private programs, who receive the lowest pay, struggle to access meaningful support, and leave the profession at high rates, compared to publicly funded programs.MethodsIn this paper, we describe the STREAMin3 birth-to-five curriculum model. We focus on describing how the curriculum model is intended to be used program-wide in infant, toddler, and preschool classroom, how the curriculum components support social, emotional, and academic skills, and how the aligned and embedded professional development model is designed to build educator capacity. We then present implementation data from the scaling of STREAMin3 during 2022 to 2023 in over 2,000 early childhood education classroom settings in Virginia that received state or federal funding.ResultsWe found that educators used and enjoyed the curriculum. Educators at private programs and family day homes reported higher satisfaction, compared to those at public programs and in early childhood special education settings. On average, educators reported implementing curriculum components two to three days a week.DiscussionWe discuss implications, including the need to support educators across settings as curricula and other initiatives are implemented at-scale across states. We discuss the need for future research to explore approaches to increase educator engagement and implementation, with attention to the unique needs of different program types.